Communicating communitarian approach - Pirla Santamaria, Alba; Julià Traveria, Ramon (Cuadernos de Trabajo Social, 2014)
In times of crisis it is good and necessary reflecting on some basic elements of our profession and to take this opportunity to relate the different actors who are constructing our daily discipline. On the one hand, the academic side, this includes professors who are responsible for teaching and research, and students, who are the future of the profession. On the other hand, the professional world comprising the heads of government and social institutions that provides social services and social welfare, and the professionals who carry out their functions. From the relationship between this set of stakeholders arise difficulties and possibilities. It is essential that the Social Work make a set of approaches that turn their threats into opportunities and strengthen our contribution to society.